A challenging case of tracheal foreign body retrieval following COVID-19 swabbing - James May; Katrina Mason; Parag Patel; Brendan Madden (Monaldi Archives for Chest Disease, 2021)
The COVID-19 pandemic has resulted in a significant increase in the number of tracheostomised patients in hospitals requiring ventilatory support. These patients require highly specialist care, but overwhelmed hospital systems with stretched human resources potentially leave these patients cared for by undertrained healthcare professionals. We describe a rare complication where a routine COVID-19 swab done incorrectly via a tracheostomy tube, resulted in a snapped-off swab in the trachea. We outline the events and our method of removal using rigid bronchoscopy through the tracheostomy stoma as endo-tracheal bronchoscopy was impossible due to significant sub-glottic stenosis. This case highlights the paramount importance of the unique care needed to safely manage tracheostomies during this ongoing pandemic.